Kerangka Kerja Keterikatan Pelanggan Terhadap Kepuasan Pelanggan : Anteseden dan Konsekuensi - Nindi Anggi Wardani; Endang Kustami (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
This study examines the relationship between requirements and framework development in Customer Engagement (CE). In this paper, it is developed based on engagement theory with the assumption that a satisfying relationship will be able to create an emotional connection so that co-workers will be involved and bound to each other. Based on theoretical studies, this paper proposes a framework that examines the components of CE, the antecedents. involved and the consequences of CE. To complement the review, we also discuss how industry type, company characteristics – Business to Business vs Business to Consumer – and value and level of involvement affect relationship satisfaction, both contributing directly and indirectly from the perspective of emotional involvement in customer engagement. Furthermore, it examines the development of Customer Engagement and how to maximize company performance by making the right strategic changes. The findings of this paper are the relationship between emotion and the indirect contribution of customer needs to be enhanced in the corporate service industry with the B2B concept for products/services with a high level of involvement; In addition, it is also necessary to improve services for products or services with a high level of brand value and companies that provide a higher level of satisfaction.